PENGARUH KINERJA KEUANGAN, FINANCING TO DEPOSIT RATIO (FDR), MODAL SENDIRI, TERHADAP PEMBIAYAAN MUDHARABAH PERBANKAN SYARIAH YANG ADA DI INDONESIA - Dinda Lestari Purba; Jalilah Ilmiha (Universitas Islam Islam Sumatera Utara, 2021)
The background to the problem of this study is the difference in each influence of the variable x on the variable y studied in Islamic commercial bank companies in Indonesia for the 2015-2019 period. The purpose of this study is to analyze the effect of ROA, FDR, Own Capital on Islamic Banking Mudharabah Financing in Indonesia in 2015-2019. The data analysis method used to test the hypothesis is descriptive analysis test, classical assumption test, multiple linear regression analysis, and hypothesis testing. The results showed that the variables ROA, FDR, and Own Capital simultaneously had a significant influence on Mudharabah Financing. Meanwhile, the effect is partially different. Own Capital has a significant effect on Mudharabah Financing. ROA and FDR have no significant effect on mudharabah financing.